Resistance training affects neuromuscular fatigue but not efficiency in elite rowers - van den Bogaard, T. B.; Bastiaans, J. J.; Hofmijster, M. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate how resistance training (RT) in a regular training program affects neuromuscular fatigue (NMF) and gross efficiency (EGROSS) in elite rowers.